BENEFICENT SELJUKIAN VIZIER SÂHİB ATA FAHREDDİN ALİ IN THE DECL İNE PERIOD OF TURKISH SELJUK STATE (H.644-687/M.1246-1288.) - Ahmet BALANTEKİN and Mehmet Suat Bal (International Journal of Eurasia Social Sciences, 2015)
Fahrettin Ali, who performed vizierate during crisis time of Turkish Seljukian State, is originally from Konya. His father’s name is mentioned as ‘Hüseyin’ and his grandfather’s name as ‘El-Hac Ebubekir el-Konevî’ in the-1927-dated endowment which was organized for Gok Madrasah pious foundations in Sivas. Executing vizierate mission during the years when Turkish Seljukian State was under the oppression of Mongols, Fahrettin Ali, while performing this ardous duty, tried –on one hand- to secure the survival of the state by establishing good relationships with Mongolians and on the other hand, tried to prevent the public to be overwhelmed with Mongol suppression and cruelty. Eventhough he lost vizierate status for a while due to a political conspiracy set up by Muinüddin Süleyman, thanks to the respect he earned in the eyes of Mongols, he continued his duty by regaining his status. Fahreddin Ali, who went down with the grief resulting from Argun Khan’s repressive tax demands, died in Nadir Village of Akşehir on Monday, on the 2nd of November in 1288. His name is commemorated even today with mercy and gratitude because of the services he carried out in Turkish Seljukian State and foundations he established in various parts of the country. Since he all the time used his wealth for charities and for the interest of public, he was memorialized with the title of ‘Ata’ (Father) for centuries in Anatolia.